2006
DOI: 10.5483/bmbrep.2006.39.4.394
|View full text |Cite
|
Sign up to set email alerts
|

Putrescine Transport in a Cyanobacterium Synechocystis sp. PCC 6803

Abstract: The transport of putrescine into a moderately salt tolerant cyanobacterium Synechocystis sp. PCC 6803 was characterized by measuring the uptake of radioactively-labeled putrescine. Putrescine transport showed saturation kinetics with an apparent K(m) of 92 +/- 10 microM and V(max) of 0.33 +/- 0.05 nmol/min/mg protein. The transport of putrescine was pH-dependent with highest activity at pH 7.0. Strong inhibition of putrescine transport was caused by spermine and spermidine whereas only slight inhibition was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 22 publications
3
10
0
1
Order By: Relevance
“…Similar studies in Synechocystis sp. strain PCC 6803 on the uptake of putrescine, a polycationic compound, have shown that the stimulation of the uptake of putrescine by NaCl or sorbitol was a result of an osmotic effect rather than an ionic effect (Raksajit et al 2006). The transport of nitrate in Synechocystis is mediated by an ABC-type transporter.…”
Section: Resultsmentioning
confidence: 99%
“…Similar studies in Synechocystis sp. strain PCC 6803 on the uptake of putrescine, a polycationic compound, have shown that the stimulation of the uptake of putrescine by NaCl or sorbitol was a result of an osmotic effect rather than an ionic effect (Raksajit et al 2006). The transport of nitrate in Synechocystis is mediated by an ABC-type transporter.…”
Section: Resultsmentioning
confidence: 99%
“…• E. coli has 31 genes known to be involved in the osmoregulation process, namely a two-component system for regulating two major porin-encoding genes [12], two Na + antiporters [4] and three active K + transport systems whose activation is determined by the environmental condition [3,13,14], and a number of transporters and synthetases for betaine [3], trehalose [15,16], putrescine and spermidine [17], respectively. σ 38 , one of the seven types of σ subunits of RNA polymerase, is a master regulator in a complex regulatory network that governs the expression of many stationary-phase-inducible genes, and was recently proposed as a global regulator in the osmoregulation network [18,19];…”
Section: Resultsmentioning
confidence: 99%
“…We tested spermine (tetramine), homospermidine (triamine), cadaverine (diamine), and putrescine (diamine). Of these polyamines, at least putrescine has been shown to be taken up by Synechocystis 6803 (30), and the uptake of spermine has been shown in another cyanobacterium (29). The addition of 0.0l or 0.1 mM spermine/homospermidine restored the RACLT of CASDC mutant to the wildtype level, while cadaverine and putrescine only slightly increased the RACLT (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Homospermidine synthase is not found, but deoxyhypusine synthase may transform putrescine into homospermidine, in certain groups of cyanobacteria (28). Like other bacteria, cyanobacteria can take up polyamines from the environment (29)(30)(31)(32) and may secrete polyamines (32).…”
mentioning
confidence: 99%